2011
DOI: 10.3390/molecules16010373
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Different Catalytic Activity of Various 1-Olefins during Ethylene/1-Olefin Copolymerization with Homogeneous Metallocene Catalysts

Abstract: This research aimed to investigate the copolymerization of ethylene and various 1-olefins. The comonomer lengths were varied from 1-hexene (1-C6) up to 1-octadecene (1-C18) in order to study the effect of comonomer chain length on the activity and properties of the polymer in the metallocene/MAO catalyst system. The results indicated that two distinct cases can be described for the effect of 1-olefin chain length on the activity. Considering the short chain length comonomers, such as 1-hexene, 1-octene and 1-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Increased activities of 18 %, 19 %, and 15 % were recorded with just a single millilitre addition of comonomers 1‐hexene, 1‐octene, and 1‐ decene respectively (see Table ). A slight decrease in activity of DEC‐4 compared to OCT‐4 is due to the steric hindrance caused by 1‐decene (1‐C 10 ) atoms . Furthermore, higher amounts of comonomer added up the short chain branching (SCB) to the copolymers, and correspond to lower DOC and T m .…”
Section: Resultsmentioning
confidence: 99%
“…Increased activities of 18 %, 19 %, and 15 % were recorded with just a single millilitre addition of comonomers 1‐hexene, 1‐octene, and 1‐ decene respectively (see Table ). A slight decrease in activity of DEC‐4 compared to OCT‐4 is due to the steric hindrance caused by 1‐decene (1‐C 10 ) atoms . Furthermore, higher amounts of comonomer added up the short chain branching (SCB) to the copolymers, and correspond to lower DOC and T m .…”
Section: Resultsmentioning
confidence: 99%
“…To test the influence of the preparation methods on 1-octene oxidation, 1 % Au/graphite was prepared using three different methods: sol-immobilization (SI), deposition-precipitation (DP), and the impregnation method (IM). Previous studies [19][20][21][22] have shown that the activity of the gold catalyst decreases dramatically when the gold particle size is increased. The smallest Au particles have demonstrated much higher activity in 1-octene oxidation.…”
Section: Effect Of Catalyst Preparation Methodsmentioning
confidence: 98%
“…As there is a significant difference between the alkenes with the chain length of C 6 and C 10 , we are interested in studying 1-octene (alkene with the chain length of C 8 ) to understand the effect of chain length on catalytic activity. Interestingly, the chain length has been reported to play a significant role in the catalytic activity during ethylene/1-olefin copolymerization [19]. Thus, the aim of this study is to investigate the oxidation of 1-octene using supported gold nanoparticles as a catalyst under solvent-free conditions and air as the oxidant.…”
Section: Introductionmentioning
confidence: 99%
“…We shall discuss the influence of this comonomer effect on copolymer intra-chain compositional heterogeneity in Section 3.5. The above findings can be attributed to the following: The above factors variedly influenced the following chemically intrinsic phenomena: (i) the zirconocenium−MAO anion separation [20,[44][45][46][47][48] (in ethylene homopolymerization) and (ii) the activation of the dormant/sleeping Zr + −H catalytic sites [20,[49][50][51][52][53][54][55][56][57]] by 1-hexene and 4M1P (in ethylene copolymerization). Hence, we observe varying homopolymerization catalyst productivities and comonomer effects, respectively.…”
Section: Polymerization Activity Versus Steric Hindrance and Boundarymentioning
confidence: 99%
“…Hence, we observe varying homopolymerization catalyst productivities and comonomer effects, respectively. Note that the closer is the ion-pair separation, the higher is the energy barrier associated with each polymerization step; hence, the less is the catalyst productivity [20,[44][45][46][47][48].…”
Section: Polymerization Activity Versus Steric Hindrance and Boundarymentioning
confidence: 99%